Huperzine A Provides Robust and Sustained Protection against Induced Seizures in Scn1a Mutant Mice - Wong, Jennifer C.; Dutton, Stacey B. B.; Collins, Stephen D.; Schachter, Steven; Escayg, Andrew (Frontiers in Pharmacology, 2016)
De novo loss-of-function mutations in the voltage-gated sodium channel (VGSC) SCN1A (encoding Nav1.1) are the main cause of Dravet syndrome (DS), a catastrophic early-life encephalopathy associated with prolonged and recurrent early-life febrile seizures (FSs), refractory afebrile epilepsy, cognitive and behavioral deficits, and a 15-20% mortality rate. SCN1A mutations also lead to genetic epilepsy with febrile seizures plus (GEFS+), which is an inherited disorder characterized by early-life FSs and the development of a range of adult epilepsy subtypes. Current antiepileptic drugs often fail to protect against the severe seizures and behavioral and cognitive deficits found in patients with SCN1A mutations. To address the need for more efficacious treatments for SCN1A-derived epilepsies, we evaluated the therapeutic potential of Huperzine A, a naturally occurring reversible acetylcholinesterase inhibitor. In CF1 mice, Hup A (0.56 or 1 mg/kg) was found to confer protection against 6 Hz-, pentylenetetrazole (PTZ)-, and maximal electroshock (MES)-induced seizures. Robust protection against 6 Hz-, MES-, and hyperthermia-induced seizures was also achieved following Hup A administration in mouse models of DS (Scn1a+/-) and GEFS+ (Scn1aRH/+). Furthermore, Hup A-mediated seizure protection was sustained during 3 weeks of daily injections in Scn1aRH/+ mutants. Finally, we determined that the muscarinic and GABAA receptors play a role in Hup A-mediated seizure protection. These findings indicate that Hup A might provide a novel therapeutic strategy for increasing seizure resistance in DS and GEFS+, and more broadly, in other forms of refractory epilepsy.